Feeding practices and sucking habits in Istanbul children a clinical study of prevalance and effects on dentition - KARGÜL, BETÜL (My University, 2003)
The purpose of this study was to determine the prevalence of feeding practices and sucking habits and their effect on dentition in Istanbul children. 173 children, aged 5 yr participated in this study. The previous breast-feeding, bottle-feeding, pacifier sucking, finger sucking habits were examined. Paired Sample Student t test and ANOVA were used for analysis. In the present study, breast-fed children exhibited bottle-feeding for mean 25.3 ± 22.4 months, pacifier sucking for mean 19.1 ± 13.3 months and finger sucking for mean 28.4 ± 16.1 months respectively. Nonbreast-fed children exhibited bottle-feeding for mean 29.4 ± 20.5 months, pacifier sucking for mean 30.1 ± 12.7 months. Nonbreast-fed children did not exhibit finger sucking. Breast-feeding, bottle-feeding, pacifier and finger sucking did not have any effect on dentition (p>0.05)
Keywords: dentition; feeding practices; pacifier; sucking habits